Overview of Haemoglobin Levels Before and After Menstruation in Female Students of STIKes Muhammadiyah Ciamis - Undang Ruhimat; Irma Miratul Hasanah; Endang Octaviana Wilujeng; Rosmiati Rosmiati (LPPM STIKes Muhammadiyah Ciamis, 2023)
Background & Objective: Menstruation is the periodic discharge of blood and body cells from the uterine wall of the vagina. The effect of menstruation is the risk of anemia in adolescents. The appearance of menstrual anemia will hurt the growth and development of adolescent girls, such as decreased concentration and learning ability, impaired growth, resulting in unsatisfactory height, decreased physical strength, and pale skin. This study aimed to determine the difference in Haemoglobin levels before and after menstruation in female students of STIKes Muhammadiyah Ciamis DIII Health Analyst Study Program. Method: This research is a descriptive study with a purposive sampling technique conducted from January to June 2021. Respondents in this study were level 2 female students year students of the D-III Health Analyst Study Program at STIKes Muhammadiyah Ciamis as many as 31 respondents—were measured using the CyanmetHaemoglobin method with the instrument used, namely the Photometer tool. The examination results were processed manually and displayed in table format for narration. Result: The examination results of Haemoglobin levels before menstruation averaged 13.1 g/dL and Haemoglobin levels after menstruation averaged 11.9 g/dL. Conclusion: It can be concluded that the average results show a decrease in Haemoglobin levels when experiencing menstruation.